Multiscale modeling of microbial degradation of outer tissues of fiber-crop stems during the dew retting process. (September 2020) - Lashermes, Gwenaëlle; Bleuze, Laurent; Recous, Sylvie; Voinot, Richard; Lafolie, François; Chabbert, Brigitte
Graphical abstract: Highlights: A multiscale model of fiber-crop stem biodegradation during dew retting is proposed. Mass loss dynamics were well simulated for outer tissues and individual polymers. Median values of kinetic parameters from bioprocesses were relevant for retting. Biodegradation was modulated by a moisture function to give consistent simulations. The maximum specific growth rate optimized for hemp retting was 11.9 per day. Abstract: Dew retting of fiber crops, such as hemp or flax, in the field after harvest promotes the microbial biodegradation of the tissues surrounding cellulosic fibers, which helps preserve the quality of fibers during their extraction and valorization for industry. This bioprocess is currently the bottleneck for plant fiber valorization because it is empirically managed and its controlling factors have not been properly quantified. A novel multiscale model representing tissue and polymer biodegradation was developed to simulate microbial growth on the stem during retting. The model was evaluated against experimental hemp retting data. It consistently simulated the mass loss of eight plant polymers belonging to two tissues of the stem outer layer, i.e., parenchyma and fiber bundles. Microbial growth was modeled by Monod equations and modulated by the functions of temperature and moisture. This work provides a tool for gaining more insights into microorganism behavior during retting under local climate conditions.